New control paradigm for both islanded and grid-connected operation of PMSG-based wind turbine - Meghdad Fazeli (The Journal of Engineering, 2019)
This article proposes a new control paradigm for the seamless operation of a permanent magnet synchronous generator (PMSG) based wind energy conversion system (WECS) in both islanded and grid-connected modes. Conventionally, grid-connected WECS are controlled to extract the maximum power from the wind, known as maximum power point tracking (MPPT). However, in islanded operation, the objective is to control the power generated from the WECS to match the load demand, which here is called load following power generation (LFPG). This article proposes a power management system (PMS) which integrates the MPPT and LFPG capabilities of the WECS into a single-control paradigm. This enables the WECS to seamlessly achieve MPPT in grid operation, LFPG in islanded mode and low-voltage ride-through (LVRT) during fault. The proposed scheme is validated using MATLAB/SIMULINK simulations.